Synthesis, spectroscopy, and photophysical properties of newly magnesium (II) phthalocyanine - Mehmet Pişkin; Ömer Faruk Öztürk; Zafer Odabaş (MANAS: Journal of Engineering)
2(3),9(10),16(17),23(24)-tetrakis-2,6-dimethoxyphenoxy substituted magnesium (II) phthalocyanine, which has very good solubility in polar and non-polar solvents and does not aggregate, was synthesized. Its structure was characterized by spectroscopic methods such as elemental analysis, UV-vis, FT-IR, MALDI-TOF mass and 1H NMR. It has very good solubility in polar aprotic solvents such as dimethyl sulfoxide, N, N- Dimethylformamide, tetrahydrofuran, dichloromethane, and non-polar solvents such as toluene, chloroform. Its aggregation properties have been studied both in the solvents mentioned above and in N, N- Dimethylformamide at different concentrations. Its photophysical properties were determined in N, N-dimethyl formamide. The effects of the nature and presence of 2,6-dimethoxyphenoxy group, which is an antioxidant derivative, on the phthalocyanine skeleton on the spectroscopic and photophysical properties were investigated by comparing it with unsubstituted magnesium (II) phthalocyanine. It can be a good nominee for various technological applications in that it does not aggregate and has good solubility in polar and non-polar solvents, as well as better and favorable fluorescence properties than its analog in the previous study.